Microsoft PowerPoint 2010 a case approach - O'Leary, Timothy J. 1947- (O'Leary, Timothy J. 1947- O'Leary series., 2011)
"The goal of the O'Leary Series is to provide you with the necessary skills to efficiently use these applications. Equally important is the goal to provide a foundation for students to readily and easily learn to use future versions of this software. This series does this by providing detailed step-by-step instructions combined with careful selection and presentation of essential concepts. Times are changing, technology is changing, and this text is changing too. As students of today, you are different from those of yesterday. You put much effort toward the things that interest you and the things that are relevant to you. Your efforts directed at learning application programs and exploring the Web seem, at times, limitless. The mission of the series is to build upon and extend this interest by not only teaching the specific application skills but by introducing the concepts that are common to all applications, providing students with the confidence, knowledge, and ability to easily learn the next generation of applications"--Provided by publisher.